(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines phraseological units containing the component “birth” in English and Uzbek languages from a comparative linguocultural perspective. The study investigates how idiomatic expressions connected with birth reflect cultural attitudes toward destiny, life success, social privilege, natural talent, and human identity. The semantic, pragmatic, metaphorical, and cultural characteristics of phraseological units are comparatively analyzed using examples collected from literary works, phraseological dictionaries, folklore materials, and spoken discourse. The findings reveal that English phraseological units connected with birth are largely associated with individuality, personal capability, inherited privilege, and social mobility, whereas Uzbek phraseological units emphasize divine determination, collectivism, family reputation, spirituality, and fatalistic worldview. The research demonstrates that phraseological units function as carriers of national mentality and cultural memory. The article contributes to the development of comparative phraseology, linguoculturology, cognitive linguistics, and intercultural communication studies.